Improving Student’s Listening Skills through (TPS) Text Prediction Strategy by QR-Code Scanning Activity - Primandana, Putu Agus (Institut Hindu Dharma Negeri Denpasar, 2020)
This study is aimed to improve the student’s listening skills through (TPS) text prediction strategy by QR-code scanning activity. The method of analyzing data in this research is to use the classroom action research study conducted using 2 circles. The subjects of the study were in SMPN 3 Selat, to the ninth students of the first semester in academic year 2019/2020 which consist of 32 students with 15 male and 17 female. This study dealt with TPS (Text Prediction strategy by QR-Code scanning activity to improve students’ listening skills. The steps were planning, action, observation, reflection. After the series of action research in teaching and learning process in cycle I and cycle II by using the (TPS) text prediction strategy by QR-code scanning activity to increase student’s listening skills of narrative text, the researcher could take some result as follows: there are significant differences we can see from the result of the study before the action and after the action, even in cycle I and cycle II activity. In cycles, the student’s minimum completeness rises from 11 students to 25 students from before cycles. After cycle II, the student’s minimum completeness is raising also to 29 Students from 25 students who passed the minimum completeness in cycle I. The number of students who still failed in reaching the minimum completeness in cycle II is only 3 students. this may be observed deeply again in the next research to find out the factors and causes about the students who still having trouble mastering listening skills